IMPACT OF INFORMATION TRANSFER ON SAFETY OF SOCIETY - Lysenko, Sergii (International Journal of Psychosocial Rehabilitation, 2020)
The article is sanctified to research of influence speed of information transfer on informative safety of society. An author extrapolates the outlined problem through the prism of laws of physics, what a conclusion allows to do about dependence of destructive energy of information on three indexes - volume, closeness and speed of distribution. In case of opposition of two (or more) opponents, possibility of informative threat is determined exactly by these parameters of the informative systems of each of them. With development of informational technologies speed of distribution of information arrives at velocity of light, that increases importance of comparison of volume and closeness of information. A researcher insists on a necessity creation of such an administrative-legal paradigm that would provide the free and safe stream of information into society, at maintenance of rights and freedoms of man and citizen.